The use of brushite calcium phosphate cement for enhancement of bone-tendon integration in an anterior cruciate ligament reconstruction rabbit model - Wen, Chun-Yi; Qin, Ling; Lee, Kwong-Man; Chan, Kai-Ming (Journal of biomedical materials research. Part B, Applied biomaterials, 2009)
This study was designed to investigate the osteoconductivity and bioresorption of brushite calcium phosphate cement (CPC) in bone‐tendon interface healing after anterior cruciate ligament (ACL) reconstruction. Surgical reconstruction using grafted tendon in bone tunnel was performed bilaterally in 28 skeletal mature rabbits. Brushite CPC was implanted between grafted tendon and bone tunnel of one limb with the contralateral one as the control. A batch of 14 rabbits was sacrificed at 6 and 12 weeks, respectively, after surgery. At each time point, six rabbits were used for micro‐CT and subsequent histological examinations, whereas the remaining eight rabbits were used for pull‐out testing. The components of brushite CPC‐dicalcium phosphate dihydrate matrix degraded rapidly with β‐tricalcium phosphate granules left for guiding new bone formation. Brushite CPC augmented the peri‐tendon bone volume and promoted bone growth into the healing interface. The ultimate strength and stiffness of the graft‐tunnel complexes on experimental side was higher than that of the control by 117% and 102%, respectively, at 6 weeks postoperatively (p < 0.05 for both). The use of brushite CPC caused a paradigm shift in failure mode from intra‐tunnel to intra‐articular portion at 12 weeks postoperatively (p = 0.013). Brushite CPC significantly enhanced the bone‐tendon integration after ACL reconstruction, which provided a scientific basis for clinical application. © 2008 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 2009